Periodization of Modern Theater in Bogor 1950-1980 - Reza Yudhistira; Tenu Permana; Muhammad Fadhilah Riandi Rachmat (Universitas Pakuan, 2025)
This study examines the development of theater in Bogor from 1950 to 1980, with an emphasis on the dynamics of performances, the formation of theater groups, and the influence of social and political changes on local cultural expression. This study uses a historical method that includes four stages, namely heuristics, criticism, interpretation, and historiography. The results show that in the 1950s, theater in Bogor was still experimental and limited to student groups with limited theoretical knowledge. However, an important momentum was created with the holding of the Drama Arts Week in 1955, which became the starting point for the development of theater in this region. In the 1960s, the emergence of theater groups such as Raksa Budaya and Tunas Muda signaled a significant change, with a more systematic and theoretical approach to staging. The influence of modern theater became increasingly apparent, especially with the establishment of the Bogor Theater Study (STB) group, which introduced a theoretical and critical approach to staging. In the 1970s, theater in Bogor was increasingly influenced by international theater developments, with dramaturgical experiments and performance forms that were more reflective of social and political conditions. This opened up space for more experimental and diverse theatrical works. This research shows that Bogor has played an important role in the history of modern Indonesian theater. Keywords: theater development, Bogor theater studies, Bogor theater, modern theater